2020
DOI: 10.3390/ijms21114009
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Triclosan Results in Abnormal Brain Development and Behavior in Mice

Abstract: Triclosan (TCS) is one of the most common endocrine-disrupting chemicals (EDCs) present in household and personal wash products. Recently, concerns have been raised about the association between abnormal behavior in children and exposure to EDC during gestation. We hypothesized that exposure to TCS during gestation could affect brain development. Cortical neurons of mice were exposed in vitro to TCS. In addition, we examined in vivo whether maternal TCS administration can affect neurobehavioral development in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…Moreover, rat administered butylparaben during the period from early pregnancy to weaning produce offspring with autism-like symptoms [ 22 ]. Perinatal exposure to triclosan induced neurodevelopment disorder and led to abnormal social behaviors, cognitive impairment, and deficits in spatial learning and memory [ 10 ]. These observations suggest that OP may also impair central nervous system development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, rat administered butylparaben during the period from early pregnancy to weaning produce offspring with autism-like symptoms [ 22 ]. Perinatal exposure to triclosan induced neurodevelopment disorder and led to abnormal social behaviors, cognitive impairment, and deficits in spatial learning and memory [ 10 ]. These observations suggest that OP may also impair central nervous system development.…”
Section: Discussionmentioning
confidence: 99%
“…For experimental design, offspring mice between 6- and 10-week age were randomly selected to perform behavior tests [ 10 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [150] and Park et al [151] both showed that perinatal TCS exposure caused porcine mitochondrial disruption and oxidative stress. Tran et al [152] demonstrated that perinatal TCS exposure induced neurodevelopment disorders in mice, leading to significant social, cognitive and learning defects in offspring mice.…”
Section: Fate and Impacts Of Triclosan And Triclosan-related Compoundmentioning
confidence: 99%
“…Briefly, it is reported that triclosan affects immune responses, cardiovascular functions, and ROS production [1]. Studies carried out in mice indicate that prenatal exposure to triclosan can induce neurodevelopmental disorders [4]. Recently, we showed that triclosan has the potential to induce neurotoxicity at sublethal concentrations by inhibiting acetylcholinesterase (AChE) enzyme in vivo [5].…”
Section: Introductionmentioning
confidence: 99%